Smart Card Stunting Media Influences Knowledge and Attitudes of Pregnant Women about Stunting Prevention - Veni Lestari; Wisuda andeka marleni; Lissa Ervina (CV Media Inti Teknologi, 2024)
Stunting is a condition when a child's height is less than the standard height for his age and is a problem of chronic malnutrition caused by insufficient nutritional intake for quite a long time. If pregnant women do not know the causes of stunting, especially nutritional adequacy in early pregnancy, it will have an impact on the attitude of pregnant women who do not apply good nutritional patterns during pregnancy. This can happen because when a child is stunted it disrupts his physical growth, immunity, and cognitive function. The purpose of this study was to determine the effect of education using the stunting smart card media on the knowledge and attitudes of pregnant women regarding stunting prevention in the work area of the Telaga Dewa Health Center, Bengkulu City. This research is a quantitative type of Pre-Experiment design with a one-group pre-test and post-test design. The sampling technique in this study was purposive sampling. The number of samples to be examined in this study were 30 first trimester pregnant women. The results showed that the average attitude score before intervention was negative, namely 28.63 and after education using a stunting smart card, a positive attitude was 37.70. The p value was obtained = 0.000 ≤ 0.05 using a confidence level of 95%, which means that there is an effect of the stunting smart card media on the knowledge and attitudes of pregnant women about stunting prevention in the work area of the Telaga Dewa Health Center, Bengkulu city.